Optimized Design of Warehousing Operation Process Based on RFID Technology (Asian Business Research, 2022)
Warehousing as one of the main functions of logistics core functions, the optimization of warehousing operationprocess has been highly valued by the entire industry. Based on RFID technology, taking Jingdong HuizhouHuiyang Logistics Center as an example, combined with the analysis of the current situation of its warehousingoperation process, the process design is optimized from the three aspects of warehousing, warehousemanagement and outbound storage, and the simulation modeling of the inbound and outbound processes iscarried out by using Flexsim software. The results show that: 1) The warehousing operations of logistics centershave pain points of long waiting time in storage, low inventory efficiency and high cargo loss rate. 2) Throughthe comparative analysis of the modeling results before and after optimization, RFID technology can effectivelyimprove the efficiency of the warehousing operation process, and determine the feasibility of the optimizedprocess to improve the efficiency of the warehousing operation process.